ANALISA PENGGUNAAN SILICAFUME, SUPERPLASTIZICER SERTA PENAMBAHAN SERBUK KACA TERHADAP PENINGKATAN MUTU BETON PADA PERENCANAAN BETON MUTU TINGGI (K-600) MENGGUNAKAN METODE STANDAR NASIONAL INDONESIA (SNI) - Amran, Yusuf; Daud, Yusuf (Prodi Teknik Sipil Universitas Muhammadiyah Metro, 2018)
In addition to the quality improvement of concrete construction materials technology,also must be able to answer and finish the environmental problems which the program greenconstruction has long been established in the world of construction included in theconstruction technology of the concrete. the use of one of the solid waste in the form offractions/glass powder is one of the alternative solutions of reducing pollution of theenvironment on the other hand are forecast to contribute in a concrete quality improvementespecially on high quality concrete This is due to the many glass powder contains one of themain chemical compounds that are required on the quality improvement of concrete namelySi (silica). This research using a sample of Test Cylinder diameter of 150 mm and a height of300 mm. Testing done when aged 7, 14, 21, and 28 days and every age consists of 3 testobjects with 5 types of variations of concrete mix so that it takes 12 test objects for eachcoarse aggregate based on the origin of where they were taken, and obtained a total of testobjects. The results showed that the influence of Silica Fume and powder glass in concretemortar can increase the kelecakan of the concrete, it is influenced by the shape of the SilicaFume particles and fine glass powder (passes sieve No. 200). On the use of Silica Fume 15%,1.5% Superplasticizer and Powder 15% Glass reinforced concrete at the age of 28 days,gained strong press optimum concrete that is the highest power of most of the other 659.590kg/cm2, these results do indeed have exceeded the quality of concrete planned (600 kg/cm2),but has not yet reached a maximum in strong concrete press namely of 706.60 kg/cm2. Withthe increased magnitude of the use of Silica Fume and powder glass obtained a small slumpvalue, due to nature of glass powder and absorb water, except for the composition of the SF20%, SP and SK 2% 20%. The use of Silica Fume and powder glass in concrete as cementreplacement with supplementary material levels > 15% of cement weight can lower thequality of the concrete, This is because the water absorption is too large by Silica Fume andpowder glass so the water needed for the hydration is not enough to result in concretestrength becomes lower. The use of Superplasticizer on the concrete mix is to simplify thework of concrete/made concrete mix became more diluted but not giving effect to qualityimprovement of concrete that will be generated.Keywords: High-Quality Concrete, Superplasticizer, Silicafume, Glass Powder